2018
DOI: 10.1021/acscatal.8b00896
|View full text |Cite
|
Sign up to set email alerts
|

Designed Self-Assembly of Peptides with G-Quadruplex/Hemin DNAzyme into Nanofibrils Possessing Enzyme-Mimicking Active Sites and Catalytic Functions

Abstract: Enzymes fold into three-dimensional structures to arrange their active groups exquisitely for the remarkable catalytic properties. We are inspired to design and assemble Gln-containing peptides with G-quadruplex DNA/hemin complexes to form the catalytic nanofibrils that possess the horseradish peroxidase-mimicking active sites and catalytic functions. Theoretical simulation results revealed that the intermolecular association of Gln peptide may result in local enrichment and proper orientation of carboxamide g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 54 publications
(88 reference statements)
0
28
2
Order By: Relevance
“…As a step forward, the same group designed β-sheet forming Gln-contained peptides (NH 2 -QQKFQ­FQFEQQ-CONH 2 , Q11) to self-assemble with oligohistidine peptide (NH 2 –HHHHHHHHHH–COOH, H10), G-quadruplex DNA (5′-GGGTA­GGGCGG­GTTGGG-3′, G-DNA) and hemin into catalytic nanofibrils (Figure A) . Theoretical simulation results revealed that the intermolecular association of Gln peptide may result in local enrichment and proper orientation of carboxamide groups, which provided potential multivalent hydrogen bonds for enhancing H 2 O 2 affinity to hemin and may behave similarly to distal Arg (the side chain guanidium can provide up to 5 hydrogen bonds) in a natural heme pocket.…”
Section: Design Fabrication and Applications Of Enzyme-mimicking Supr...mentioning
confidence: 99%
“…As a step forward, the same group designed β-sheet forming Gln-contained peptides (NH 2 -QQKFQ­FQFEQQ-CONH 2 , Q11) to self-assemble with oligohistidine peptide (NH 2 –HHHHHHHHHH–COOH, H10), G-quadruplex DNA (5′-GGGTA­GGGCGG­GTTGGG-3′, G-DNA) and hemin into catalytic nanofibrils (Figure A) . Theoretical simulation results revealed that the intermolecular association of Gln peptide may result in local enrichment and proper orientation of carboxamide groups, which provided potential multivalent hydrogen bonds for enhancing H 2 O 2 affinity to hemin and may behave similarly to distal Arg (the side chain guanidium can provide up to 5 hydrogen bonds) in a natural heme pocket.…”
Section: Design Fabrication and Applications Of Enzyme-mimicking Supr...mentioning
confidence: 99%
“…[18][19][20][21] Unfortunately, the performances of G4-DNAzymes are still below those of corresponding enzymes, leading to new research and strategies for improved performance. To date, optimization strategies can be divided into two types: the addition of exogenous activators, [22][23][24][25][26][27][28][29] such as spermine, 22 cytidine triphosphate (CTP), 23 adenine triphosphate (ATP), [23][24][25] templateassembled synthetic G-quartet (TASQ), 26 and self-assembling peptides [27][28][29] on one side, and the modification of the G4 structure [30][31][32][33][34][35] to provide hemin with a more defined and suited binding pocket 31,32 or hemin itself 36,37 on the other side. The latter mostly focuses on the modification of the so-called parallel G4 structure, in which all constitutive DNA strands are codirectionally oriented and the structure displays fairly accessible G-quartets, the privileged hemin-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrin molecular self-assembly using cooperative coassembly becomes a popular technique for developing and synthesizing multicomponent photosensitizing materials. , Hemin, as a Fe-containing porphyrin, is the U.S. Food and Drug Administration (FDA)-approved drug for acute intermittent porphyria since 1983. , In recent years, hemin has been widely used in the field of catalysis research because of its mimetic peroxidase activity. Most importantly, hemin possessed three attractive functions in cancer therapy: (1) Fenton catalytic activity, (2) mimetic peroxidase characteristic that could catalyze H 2 O 2 to generate O 2 , ,, and (3) GSH-depletion capacity. , Thus, based on the well-established evidence, we hypothesized that the hemin-based PS nanomaterial could effectively catalyze endogenous H 2 O 2 to produce O 2 and • OH at the tumor site, thereby enhancing the efficacy of PDT/CDT and simultaneously eliminating the intracellular GSH and inhibiting the activity of GPX4 from inducing ferroptosis. Although some groups used the PDT/CDT/ferroptosis combination therapy approach to obtain successful cancer therapy, , the rational design of hemin-based self-assembly porphyrin nanoparticles that combine all these ideal functions has not been reported to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%